Meta-analysis of the effects of the dietary inclusion of brewers grains on feed intake, milk yield, and feed efficiency of lactating dairy cows - S.C. Chelkapally; T.H. Terrill; I.M. Ogunade; Z.M. Estrada-Reyes; A.A. Pech-Cervantes (JDS Communications)
Distillery byproducts such as brewers grains (BG) have been widely used in dairy cow diets for decades to reduce diet costs and improve nutrient efficiency. Thus, the objective of this study was to evaluate the magnitude of the effects of dietary supplementation with BG on feed intake (DMI), digestibility, milk yield (MY), and feed efficiency (FE) of lactating dairy cows. A total of 12 peer-reviewed articles (n = 472 dairy cows) from 1983 to 2021 were collected systematically with the PRISMA method. The weighted raw mean differences (RMD) between dietary BG and control treatments were estimated with a robust variance estimation. Likewise, diet characteristics, such as CP content, NDF content, type of BG (wet = 1 and dry = 2), DIM, and BG inclusion rate (0 to 75%) were used as covariates in a meta-regression, subset, and dose-response analysis. Compared with the control, dietary BG decreased DMI (19.7 vs. 20.2 kg/d) and tended to increase MY (28.9 vs. 28.4 kg/d), but no effects were observed on FCM yield (29.1 vs. 28.8 kg/d), milk fat (3.8 vs. 3.7%), and milk protein (3.2 vs. 3.2%) concentrations. However, dietary BG increased FE (1.45 vs. 1.34 FCM/DMI) without influencing total-tract DM (61.9 vs. 55.7%) and NDF (49.7 vs. 54.5%) digestibility. Increasing the inclusion rate of BG linearly increased (R2 = 0. 554) dietary NDF. Thus, the dose-response analysis revealed that feeding up to 20% BG (dietary NDF = 39%) to lactating dairy cows increased MY and FE. Overall, this meta-analysis supports the hypothesis that dietary BG improved FE in lactating dairy cows.